1992
DOI: 10.1111/j.1651-2227.1992.tb12390.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral gentamicin is not effective treatment for persistent diarrhea

Abstract: We conducted a randomized, double‐blind, placebo controlled clinical trial of oral gentamicin (10 milligrams/kilogram body weight/day for five days) in treatment of unselected cases of persistent diarrhea (duration 14‐18 days at initiation of treatment) among 3‐36‐month‐old children in a rural Guatemalan community. Following random assignment of each child to a treatment group, the appropriate dose of gentamicin or placebo was administered to the child three times daily by a study nurse; this nurse also identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 17 publications
1
34
1
Order By: Relevance
“…Our study confirms the lack of efficacy of antibiotics in the treatment of diarrhea as observed in those studies (15,16). Addionally, we analyzed patients with severe diarrhea, most of them in their first semester of life, characteristic that differentiates our study from the previous ones (15,16). Bhatnagar et al (16) It should be emphasized that exclusive breast-feeding may decrease the risk of acute and persistent diarrhea, since human milk has protective properties against diarrhea such as avoidance of exposure to bacteria, antimicrobial agents, anti-inflammatory and immunomodulating factors and promotion of healthy microflora (4).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Our study confirms the lack of efficacy of antibiotics in the treatment of diarrhea as observed in those studies (15,16). Addionally, we analyzed patients with severe diarrhea, most of them in their first semester of life, characteristic that differentiates our study from the previous ones (15,16). Bhatnagar et al (16) It should be emphasized that exclusive breast-feeding may decrease the risk of acute and persistent diarrhea, since human milk has protective properties against diarrhea such as avoidance of exposure to bacteria, antimicrobial agents, anti-inflammatory and immunomodulating factors and promotion of healthy microflora (4).…”
Section: Discussionsupporting
confidence: 80%
“…However, antimicrobials may be useful in reducing associated enteric symptoms, including watery diarrhea and/or dysentery or fever in the more severe cases of illness and in the management of persistent diarrhea (37). The studies of Bartlett et al (15) and Bhatnagar et al (16), both of them controlled, demonstrated respectively the lack of clinical efficacy of gentamicin in children with persistent diarrhea in the community and in hospitalized patients with mild to moderate cases of diarrhea. Our study confirms the lack of efficacy of antibiotics in the treatment of diarrhea as observed in those studies (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations